Pengaruh Motivasi, Kompetensi, Dan Kompensasi Terhadap Kinerja Karyawan Bank Syariah Mandiri - Rike Selviasari (Universitas Islam Kadiri, 2018)
This study analyzes the effect of motivation, competency, and compensation on the performance of Islamic bank employees in this research conducted at Bank Syariah Mandiri, Kediri Regency. This study uses a survey method using primary data obtained from the questionnaire. The sample in this study were 35 employees. The sample is taken by saturated sample is a sampling technique if all members of the population are used as samples. The analysis technique in this study used multiple linear regression. The results of this study indicate that the variables of motivation, competence, and compensation partially have a significant effect on employee performance. While simultaneously the variables of motivation, competence, and compensation have a significant effect on employee performance at a significance level smaller than 0.05 (0,000 <0.05). The results also show that the most dominant Motivation variable on employee performance with the value of β is 0.422 and the significance value is smaller than 0.05 (0.006 <0.05)